The TTC-technique might not appropriately test the physiological stage of plant tissues - Busso, Carlos Alberto (2015)
The 2,3,5triphenyltetrazolium chloride (TTC) technique has been used during decades to distin guish between dead and alive tissues of perennial grasses. This technique did not consider, however, that dormant (i.e., viable) tissues could exist within those erroneously considered dead tissues, thus being unable to report the true physiological stage of those plant tissues. Development of a procedure able to distinguish between metabol ically active or dormant or dead tissues is then critical. This study developed a procedure to classify plant tissues of perennial grasses (Poa ligularis (Nees ex Steud.), Nassella longiglumis (Phil.) Barkworth, Amelichloa ambigua (Speg.) Arriaga & Barkworth, and Piptochaetium napostaense (Speg.) Hack.) in a more appropriate physiologi cal stage (i.e., metabolically active, dormant or dead) than the traditional TTCtechnique. Perennial grass seeds or meristematic buds were immersed in a TTC solution to obtain metabolically active (red or pink staining) or unstained (either dormant or dead) tissues. TTCunstained tissues were placed in Evans Blue solution to sepa rate dormant from dead tissues. The combination of TTC and Evans Blue techniques allowed the separation of metabolically active, dormant or dead tissues. Use of Evans Blue on TTCunstained seeds and buds allowed to determine that some of these tissues were not dead but dormant (i.e., viable). Among the TTCunstained tissues between 2 to 35% of total grass seeds and from 19.5 to 42% of all evaluated buds were dormant (viable and poten tially able to growout) but not dead. Combination of TTC and Evans Blue techniques allowed a better classifi cation of the physiological stages of plant tissues (metabolically active, dormant or dead) than the conventional TTC test.